Worsened Tricuspid Regurgitation Following Pericardiectomy for Constrictive Pericarditis. (5th October 2021) - Tabucanon, Ray S.; Wang, Tom Kai Ming; Chetrit, Michael; Furqan, Muhammad M.; Chan, Nicholas; Pande, Amol; Jellis, Christine L.; Cremer, Paul C.; Kwon, Deborah H.; Johnston, Douglas; Klein, Allan L.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Worsening tricuspid regurgitation (TR) severity may occur after pericardiectomy surgery for constrictive pericarditis patients; however, its mechanisms and predictors are not well established. We evaluated the clinical characteristics, associated factors, and outcomes of worsening TR after pericardiectomy. Methods: Consecutive patients undergoing pericardiectomy for constrictive pericarditis without tricuspid valve surgery and with pre- and postoperative echocardiography available during 2000 to 2017 were retrospectively studied. Clinical, imaging, hemodynamic, and mortality characteristics were analyzed by those with and without worsening TR by at least one grade. Results: Among 381 patients (age 61 [17] years, 318 [83.5%] male), 193 (50.7%) had worsening TR post-operatively, and 75 died during the 2.5 (5.4) years follow-up. In univariable analysis, worsening TR was associated with a history of congestive heart failure (47.2% versus 31.9%, P =0.003), increased left atrial volume indexed (23 versus 20 mL/m 2, P =0.020), reduced right ventricular fractional area change (47% versus 54%, P <0.001), and worsening mitral regurgitation (39.7% versus 16.6%, P <0.001). Worsened TR had a trend toward reduced survival during follow-up (log-rank P =0.080), especially those with worsened TR but no recovery of TR grade on subsequent echocardiography within the first year compared with those without worsened TR (log-rank P =0.02). In multivariable analysis, right ventricular fractional area change, left atrial volume indexed, left ventricular mass indexed, pulmonary artery systolic pressure, and right atrial pressure/pulmonary capillary wedge pressure ratio were most associated with worsened TR, while blood urea nitrogen, hematocrit, lateral and medial e' tissue Doppler and heart rate were most associated with mortality during follow-up. Conclusions: Worsening TR severity was prevalent after pericardiectomy and had a trend toward reduced survival, especially if TR severity did not recover on subsequent echocardiography. Presence of parameters associated with worsened TR and reduced survival should alert clinicians to carefully manage these patients during follow-up.